2010
DOI: 10.2308/jis.2010.24.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Data Visualization: New Directions for Accounting Information Systems Research

Abstract: Many companies today utilize interactive data visualization to present accounting information to external users on their investor relations websites and to internal users in applications such as enterprise resource planning, Balanced Scorecard, network security, and fraud detection systems. We develop a taxonomy for examining the current state of interactive data visualization research related to accounting decision making. We organize our review around three themes: the relationship between task characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(60 citation statements)
references
References 73 publications
1
57
0
2
Order By: Relevance
“…Managers should be aware that some knowledge can be configured into more than one type of format. For example, interactive data visualization enables users to choose what format they prefer (Dilla et al, 2010). Of course, not all knowledge will have this flexibility but efforts made toward improving this flexibility benefit the organization in the long run.…”
Section: Discussionmentioning
confidence: 96%
“…Managers should be aware that some knowledge can be configured into more than one type of format. For example, interactive data visualization enables users to choose what format they prefer (Dilla et al, 2010). Of course, not all knowledge will have this flexibility but efforts made toward improving this flexibility benefit the organization in the long run.…”
Section: Discussionmentioning
confidence: 96%
“…Dilla, Janvrin et al [40] identified a series of cross-discipline research articles focused on interactive data visualization building the evidence of interactivity, information navigation and selection impact on decision-making process and outcome. They also identified a series of mostly marketing research suggesting benefits of interactive visualization: allow decision makers to navigate through complex data sets and decision accuracy through considerations of multiple factors, increase control over the data flow, enable the restructuring of the information environment, and lower the cognitive cost.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It has been noted [33] that this body of research resulted in formulation of Cognitive Fit Theory [63][64][65], that suggests the importance of fit between the problem representation and the problem-solving task in achieving effective performance [33,40,54,[66][67][68][69]. Cognitive Fit Theory is a native IS theory that came about as a reaction to the inability to rationalize the findings from previous empirical research [66] that compared decision performance in simple tasks across tabular and graphical presentation formats.…”
Section: Representationmentioning
confidence: 99%
“…Although the mandate explicitly states that public accountants are not required to provide assurance on these XBRL-related documents, early research (i.e., Bartley et al 2009Bartley et al , 2011Debreceny et al 2010;Weirich and Harrast 2010;Du et al 2011) finds that several documents contain errors. Further, new interactive data visualization software allows for the presentation of individual values from the financial statements (Dilla et al 2010;Janvrin et al 2011). Without assurance that these tags are appropriately mapped to each value, investors may be misled.…”
Section: Responses To Specific Questions In the Releasementioning
confidence: 99%